Living with Cat and Dog Increases Vaginal Colonization with E. coli in Pregnant Women - Jakob Stokholm; Susanne Schjørring; Louise Pedersen; Anne Louise Bischoff; Nilofar V. Følsgaard; Charlotte Giwercman Carson; Bo Chawes; Klaus Bønnelykke; Anne Mølgaard; Karen A. Krogfelt; Hans Bisgaard (2012)
Furred pets in the household are known reservoirs for pathogenic bacteria, but it is not known if transmission of bacteria between pet and owner leads to significantly increased rate of infections. We studied whether cats and dogs living in the household of pregnant women affect the commensal vaginal flora, and furthermore the need for oral antibiotics and rate of urinary tract infections during pregnancy.